Tactics of rehabilitation treatment for the knee articular cartilage defects after arthroscopic microfrakturing - Roy, Iryna; Bayandina, Оlena; Kostogryz, Oleg; Katyukova, Lydia (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
One of the methods of treatment in patients with the knee cartilage defects is microfracturing, and postoperative management of these patients is critical in ensuring of optimal outcomes. Objective: To increase an effectiveness of rehabilitation in patients with the knee articular cartilage defects after arthroscopic microfracturing due to development and implementation of a program for postoperative rehabilitation. Methods: We proposed a program of rehabilitation treatment consisting of four periods. Task of the first of them (early postoperative — 6 weeks) is to protect a fibrin clot formed during surgery. They improve movement in passive mode without any axial load. Criterion of the transition to the next period is time after the operation. The second period (late postoperative — 7–12 weeks): restoration of range of motion. Its objective is restoration of muscle function. Criterion of the transition is time after the operation. The third period (13–18 weeks): restoration of muscle force characteristics. Criterion of the transition is restoration of operated extremity muscle strength of 85 % or more of the healthy one. The fourth period: restoration of sport skills and returning to sport loads (over 19 weeks). Stopping criterion for rehabilitation treatment is hopping test on operated extremity 85 % of the healthy one. Feature of the program is early recovery of function without any axial load with help of mechanotherapy providing an environment for the formation of cartilage tissue in the defect zone. Outcomes were analyzed in 46 patients: in I group (18) they use the program developed; in II group (28) they did not step on the operated extremity for 6 weeks. Conclusion: The proposed program enabled a pathogenetically substantiated effective rehabilitation treatment ensuring conditions for the reparative processes in articular cartilage after microfracturing and allowing to get good functional results.